The role of school counselors in forming student becoming a digital citizen - Anastasia Dewi Anggraeni (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
The Internet is a technology that continued to develop. The development of Internet applications as if ceaselessly. Starting from electronic mail applications known as email, online games, to social networking, such as: twitter, path, Instagram, Facebook, and so forth. The Internet gives a lot of influence to human life. On the one hand, it provides a variety of conveniences for its users, but also gives a negative impact. The development of 21st century technology demands all elements throughout the world of education to utilize technology on all aspects. Digital Citizenship is a concept that helps school counselor and parents to know what students should know about using technology properly. Digital citizenship is the norm of using true and responsible technology. The role of school counselor is required to able the technology for guide students to become good citizen digital models, and the most important is how to form the habit of accessing the digital world in a safe way.